Determination of Tetracycline, Oxytetracycline, Sulfadiazine, Norfloxacin, and Enrofloxacin in Swine Manure Using a Coupled Method of On-Line Solid-Phase Extraction with the UHPLC-DAD - Mohamed S. Gaballah; Xin Li; Zijia Zhang; Abdulaziz Al-Anazi; Hui Sun; Mostafa Sobhi; Mperejekumana Philbert; Mohamed A. Ghorab; Jianbin Guo; Renjie Dong (MDPI AG, 2021)
The use of various veterinary antibiotics (VAs) in animal husbandry raises serious concerns about the development of antibiotic resistance. Antibiotics such as tetracycline, oxytetracycline, sulfadiazine, norfloxacin, and enrofloxacin are the most frequently used antimicrobial compounds in animal husbandry and generate large eco-toxicological effects; however, they are still difficult to determine in a complex matrix such as swine manure. This study has developed an effective method for detecting five VAs in swine manure using Ultra-High-Performance Liquid Chromatography-Diode Array Detector (UHPLC-DAD) coupled with on-line solid-phase extraction (SPE). The results show that the mobile phase of ACN/0.01 M oxalic acid was the optimum at pH 3.0. VAs in a swine manure matrix were extracted using solid extraction buffer solution (T3) with 97.36% recovery. Sensitivity, accuracy, and precision were also evaluated. The validity study showed good linearity (R2 > 0.99). Limit of detection (LOD) was found to be from 0.1 to 0.42 µg mL−1 in the liquid fraction and from 0.032 to 0.58 µg g−1 dw in the solid fraction. The corresponding values of the limit of quantification (LOQ) ranged from 0.32 to 1.27 µg mL−1 for the liquid fraction and from 0.096 to 1.77 µg g−1 dw for the solid fraction. Therefore, the proposed method showed the potential applicability for detecting different antibiotic compounds from swine manure samples.